Bad Bunny y Bach: Mitos e imaginarios culturales (2021)
This paper explores the notion of myth and collective imaginary as manifested in the figures of Bad Bunny (1994-) and Johann Sebastian Bach (1685-1750).  Bad Bunny has been identified as the depositary of an imaginary that situates reggaeton as a musical genre that marks the moral decadence of the culture.   Bach, on the other hand, leads the canon of composers who make classical music a paradigm of cultured and elaborated Musical Art.  The discussion suggests that both representations are part of a mythology that hides complex issues such as class discrimination and violent cultural hegemonies.  The conclusions point to the demystification of both musicians as a strategy to not only appreciate their music in a more balanced way, but also to address social issues, without the fanaticism that both musical communities promote in their myths.